Split-Cre-mediated GFP expression as a permanent marker for flagellar fusion of Trypanosoma brucei in its tsetse fly host - Ruth Etzensperger; Mattias Benninger; Berta Pozzi; Ruth Rehmann; Arunasalam Naguleswaran; Gabriela Schumann; Jan Van Den Abbeele; Isabel Roditi (mBio)
ABSTRACT Trypanosomes have different ways of communicating with each other. While communication via quorum sensing, or by the release and uptake of extracellular vesicles, is widespread in nature, the phenomenon of flagellar fusion has only been observed in Trypanosoma brucei. We showed previously that a small proportion of procyclic culture forms (corresponding to insect midgut forms) can fuse their flagella and exchange cytosolic and membrane proteins. This happens reproducibly in cell culture. It was not known, however, if flagellar fusion also occurs in the tsetse fly host, and at what stage of the life cycle. We have developed a split-Cre-Lox system to permanently label trypanosomes that undergo flagellar fusion. Specifically, we engineered trypanosomes to contain a GFP gene flanked by Lox sites in the reverse orientation to the promoter. In addition, the cells expressed inactive halves of the Cre recombinase, either N-terminal Cre residues 1–244 (N-Cre) or C-terminal Cre residues 245–343 (C-Cre). Upon flagellar fusion, these Cre halves were exchanged between trypanosomes, forming functional full Cre and flipping reverse-GFP into its forward orientation. We showed that cells that acquired the second half Cre through flagellar fusion were permanently modified and that the cells and their progeny constitutively expressed GFP. When tsetse flies were co-infected with N-Cre and C-Cre cells, GFP-positive trypanosomes were observed in the midgut and proventriculus 28–34 days post-infection. These results show that flagellar fusion not only happens in culture but also during the natural life cycle of trypanosomes in their tsetse fly host.IMPORTANCEWe have established a procedure to permanently label pairs of trypanosomes that transiently fuse their flagella and exchange proteins. When this occurs, a reporter gene is permanently flipped from the “off” to the “on” position, resulting in the production of green fluorescent protein. Crucially, green trypanosomes can be detected in tsetse flies co-infected with the two cell lines, proving that flagellar fusion occurs in the host. To our knowledge, we are the first to describe a split-Cre-Lox system for lineage tracing and selection in trypanosomes. In addition to its use in trypanosomes, this system could be adapted for other parasites and in other contexts. For example, it could be used to determine whether flagellar fusion occurs in related parasites such as Leishmania and Trypanosoma cruzi or to monitor whether intracellular parasites and their hosts exchange proteins.